Antibiotic resistance profiles of Acinetobacter baumannii isolates from surgical wound infections at Kamuzu Central Hospital in Malawi:a retrospective study - Chitandale, Edwin; Choonara, Faheema; Mwenyephiri, George; Zulu, Mike; Chisale, Master; Kipandula, Wakisa (International Journal of Research in Medical Sciences, 2019)
Background: Acinetobacter baumannii has emerged as one of the most significant pathogen due to its ability to develop antimicrobial resistance to a broad range of commonly available antibiotics. It represents a serious iatrogenic complication of modern healthcare, where patients acquire infections in healthcare facilities with limited treatment options, resulting in increased morbidity, mortality and health costs. Methods: In this retrospective study, results of culture and antimicrobial susceptibility tests of samples collected from surgical wounds of patients from January to December 2017 were extracted from Laboratory information management system at Kamuzu Central Hospital (KCH) in Malawi. Results: This study ranks A. baumannii as the fourth common cause of surgical wound infections at KCH, with a prevalence of 12.3%. Other most prevalent isolates were: E. coli (25.9%), S. aureus (25.9%) and Proteus species (17.5%). All A. baumannii isolates were resistant to Amoxicillin/Clavulanate and Ceftriaxone; 96.4% were resistant to Ampicillin; 92.9% were resistant to Gentamycin, Ceftazidime and Sulphamethoxazole-trimethoprim; 89.3% were resistant to Ciprofloxacin; and 85.7% were resistant to Cefuroxime and Piperacillin/Tazobactam; while 17.9% were resistant to Meropenem. A total of 82% of the A. baumannii isolates were Multi-Drug Resistant (MDR), while 14% were Extremely Drug Resistant (XDR). Conclusion: The emergence of MDR and XDR A. baumannii at KCH calls for rational use of available antibiotics and regular monitoring of antimicrobial resistance patterns to prevent dissemination of current strains and emergence of new resistant strains.